Pharmacology of Drugs Used as Stimulants. (15th August 2021) - Docherty, James R.; Alsufyani, Hadeel A.
Abstract: Psychostimulant, cardiovascular, and temperature actions of stimulants involve adrenergic (norepinephrine), dopaminergic (dopamine), and serotonergic (serotonin) pathways. Stimulants such as amphetamine, 3, 4‐methylenedioxymethamphetamine (MDMA), or mephedrone can act on the neuronal membrane monoamine transporters NET, DAT, and SERT and/or the vesicular monoamine transporter 2 to inhibit reuptake of neurotransmitter or cause release by reverse transport. Stimulants may have additional effects involving pre‐ and postsynaptic/junctional receptors for norepinephrine, dopamine, and serotonin and other receptors. As a result, stimulants may have a wide range of possible actions. Agents with cocaine or MDMA‐like actions can induce serious and potentially fatal adverse events via thermodysregulatory, cardiovascular, or other mechanisms. MDMA‐like stimulants may cause hyperthermia that can be life threathening. Recreational users of stimulants should be aware of the dangers of hyperthermia in a rave/club environment.